Syarat-Syarat Profesi Keguruan Menurut Perspektif Pendidikan Islam - Busthomi, Yazidul; A’dlom, Syamsul (Jurnal Pendidikan Islam, 2022)
The term profession in everyday life is used to indicate a person's work. A person who works as a doctor is said to be a doctor and a person whose job is to teach is said to be a teacher. So the term profession in this context has the same meaning as work or tasks that are carried out by someone in everyday life. Meanwhile, in professional terminology, it means a job that requires higher education for the perpetrators, which emphasizes mental work, namely the existence of theoretical knowledge requirements as an instrument for doing practical work, not manual work. So a profession must have three main pillars, namely knowledge, expertise, and academic preparation. The requirements of the teaching profession according to the perspective of Islamic education, are as follows: 1. Positions that involve intellectual activity, 2. Positions that involve a specific body of knowledge, 3. Positions that require long professionalpreparation, 4. Positions that require training in Continuous positions, 5. Positions that promise a life career in permanent membership, 6. Positions that determine their own standards, 7. Positions that prioritize service over personal gain, 8) Positions that have a strong and well- established professional organization.